CROSS-CULTURAL MUSICAL TRANSFORMATION: SHAPING CHINESE TRADITIONS - Junyi, Liu (Scientific Journal of Polonia University, 2023)
This article endeavors to thoroughly examine the processes of Western influence on Chinese musical culture, focusing on the perspectives of prominent figures within the Chinese composer-performer tradition. Specifically, it highlights the role of Westernization as a means of shaping musical concepts in the works of Fei Shi, Ou Man, Qing Zhu, and Zeng Zhizhi. Furthermore, it acknowledges that a substantial number of music scholars pursue education abroad with the intention of delving into Western musical experiences and engaging with the resources of Western musical culture and the arts. Upon their return, whether they adopt a “Westernized” or “reformed” approach, they are actively contributing to the practical development of their own musical culture and innovative musical ideas. It is revealed that the processes of Westernization primarily occurred through the efforts of individual representatives within the Chinese community. The article highlights their practical actions involving the adaptation and creation of contemporary styles and forms within Chinese musical culture.